Optimizing atoh1-induced vestibular hair cell regeneration - Staecker, Hinrich; Schlecker, Christina; Kraft, Shannon; Praetorius, Mark; Hsu, Chi; Brough, Douglas E. (The laryngoscope, 2014)
Objectives/Hypothesis Determine the optimal design characteristics of an adenoviral (Ad) vector to deliver atoh1 and induce regeneration of vestibular hair cells. Study Design Evaluation of a mouse model of intralabyrinthine gene delivery. Tissue culture of mouse and human macular organs. Methods Macular organs from adult C57Bl/6 mice were treated with binding modified and alternate adenovectors expressing green fluorescent protein (gfp) or luciferase (L). Expression of marker genes was determined over time to determine vector transfection efficiency. The inner ear of adult mice was then injected with modified vectors. Expression of gfp and distribution of vector DNA was followed. Hearing and balance function was evaluated in normal animals to ensure safety of the novel vector designs. An optimized vector was identified and tested for its ability to induce hair cell regeneration in a mouse vestibulopathy model. Finally, this vector was tested for its ability to induce hair cell regeneration in human tissue. Results Ad5 serotype-based vectors were identified as having a variety of different binding capacities for inner ear tissue. This makes it difficult to limit the dose of vector due to entry into nontargeted cells. Screening of rare adenovector serotypes demonstrated that Ad-based vectors were ideally suited for delivery to supporting cells; therefore, they were useful for hair cell regeneration studies. Utilization of an Ad28-based vector to deliver atoh1 to a mouse model of vestibular loss resulted in significant functional recovery of balance. This vector was also capable of transfecting human macular organs and inducing regeneration of human vestibular hair cells in vitro. Conclusions Improvement in vector design can lead to more specific cell-based delivery and reduction of nonspecific delivery of the trans gene, leading to the development of optimized molecular therapeutics to induce hair cell regeneration. Level of Evidence N/A. Laryngoscope 124:S1-S12, 2014